2019
DOI: 10.1186/s40359-019-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social networking addiction and academic performance in Iranian students of medical sciences: a cross-sectional study

Abstract: Background: Social networks have had a major influence on students' performance in recent years. These networks create many opportunities and threats for students in various fields. Addiction to social networking and its impact on students' academic performance caused the researcher to design and conduct this study. The purpose of this study was to investigate the relationship between social networking addiction and academic performance of students in Iran. Methods: In this cross-sectional study, 360 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
149
4
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(185 citation statements)
references
References 49 publications
19
149
4
13
Order By: Relevance
“…A relevant finding explained how social media are an important aspect of today's adolescents, offering efficiency if properly utilized [23]. A similar study on social networking identified that SNS addiction was higher in male than in female students [24].…”
Section: Discussionmentioning
confidence: 99%
“…A relevant finding explained how social media are an important aspect of today's adolescents, offering efficiency if properly utilized [23]. A similar study on social networking identified that SNS addiction was higher in male than in female students [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings showed that the number of social media used is not a significant predictor of students' academic procrastination. Researchers are of the opinion that it is when social media is poorly managed that it can lead to academic problems (Azizi, Soroush, & Khatony, 2019). This may imply that other beneficial use of social media in academics could be intervening variables.…”
Section: Discussionmentioning
confidence: 99%
“…For extreme social media use to qualify as a ‘use disorder’ requires observation of the set of signs and symptoms consistent with all addictive behaviours. Tolerance, withdrawal, conflict, salience, and relapse have been explored in individuals using validated questionnaires such as Young’s Internet Addiction Test (IAT) [ 17 ] and the Bergen Social Media Addiction Scale (BSMAS) [ 12 ]. Of all the symptoms normally associated with dependence, withdrawal following the interruption of social media use was the most prominent [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%